THE EFFECT OF ADDING CHITOSAN ON THE MECHANICAL PROPERTIES OF ECO-FRIENDLY PLASTICS BASED ON PLA/PCL - Alfatasya, Dinda; Suryani, S (Politeknik Negeri Lhokseumawe, 2023)
ABSTRACTResearch into making eco-friendly plastic has been developed because it is environmentally friendly and renewable. In this research, eco-friendly plastic was made from Polylactic Acid (PLA) and Polycaprolactone (PCL) with the addition of chitosan as a filler. The aim of this research is to study and determine the effect of mixing variations in PLA/PCL/chitosan composition on the mechanical properties of eco-friendly plastic using a hot press at a temperature of 200 0C for 1 hour. The PLA/PCL variations are 2/8 g, 3/7 g, 5/5 g, 7/3 g and 8/2 g while the chitosan composition is 0.2 g, 0.3 g, 0.4 g, 0, 5 g and 0.6 g. The characteristics of eco-friendly plastic can be seen through biodegradation tests, tensile strength tests, elongation tests, functional group tests and plastic film morphology tests. The results of the characterization of eco-friendly plastic with optimal performance are a composition of PLA/PCL/Chitosan 8/2/0.6 grams which produces 38.8% degradation percentage, a tensile strength value of 42.53 MPa with a composition of PLA/PCL/Chitosan 8 /2/0.4 grams, elongation percentage of 6.96% with a PLA/PCL/Chitosan composition of 8/2/0.2 grams. Meanwhile, the functional groups contained are the N – H, C – H, C = O and C – O groups. The results of the identification of functional groups show that no new functional groups are formed, but only a mixing process without any reaction in the constituent materials. Based on the results of the morphology test, it shows that the sample has a smooth surface. However, there is still chitosan that does not dissolve because the mixing process is not homogeneous.Keywords: Chitosan, Polycaprolactone (PCL), Polylactic Acid (PLA)